Zinc Supplementation Attenuates Cardiac Remodeling after Experimental Myocardial Infarction - Gonçalves, Andrea F. [UNESP]; Polegato, Bertha F. [UNESP]; Fernandes, Ana Angélica [UNESP]; Ishikawa, Larissa Lumi [UNESP]; Okoshi, Katashi [UNESP]; Bazan, Silméia G. Z. [UNESP]; Minicucci, Marcos F. [UNESP]; Azevedo, Paula S. [UNESP]; Ikoma, Maura R.; Penitenti, Marcimara; Chiuso-Minicucci, Fernanda [UNESP]; R Paiva, Sergio A. [UNESP]; et al. (Karger Publishers, 2018)
Background/Aims: The objective of our study was to evaluate the effects of zinc supplementation on cardiac remodeling following acute myocardial infarction in rats. Methods: Animals were subdivided into 4 groups and observed for 3 months: 1) Sham Control; 2) Sham Zinc: Sham animals receiving zinc supplementation; 3) Infarction Control; 4) Infarction Zinc. After the followup period, we studied hypertrophy and ventricular geometry, functional alterations in vivo and in vitro, changes related to collagen, oxidative stress, and inflammation, assessed by echocardiogram, isolated heart study, western blot, flow cytometer, morphometry, and spectrophotometry. Results: Infarction induced a significant worsening of the functional variables. On the other hand, zinc attenuated both systolic and diastolic cardiac dysfunction induced by infarction. Considering the infarct size, there was no difference between the groups. Catalase and superoxide dismutase decreased in infarcted animals, and zinc increased its activity. We found higher expression of collagens I and III in infarcted animals, but there was no effect of zinc supplementation. Likewise, infarcted animals had higher levels of IL-10, but without zinc interference. Nrf-2 values were not different among the groups. Infarction increased the amount of Treg cells in the spleen as well as the amount of total lymphocytes. Zinc increased the amount of CD4+ in infarcted animals, but we did not observe effects in relation to Treg cells. Conclusion: zinc attenuates cardiac remodeling after infarction in rats; this effect is associated with modulation of antioxidant enzymes, but without the involvement of collagens I and III, Nrf-2, IL-10, and Treg cells.
Keywords: Chronic remodeling; Coronary occlusion; Function; Hypertrophy; Treg cells; Zinc